Emerging responses implemented to prevent and respond to violence against women and children in WHO European member states during the COVID-19 pandemic: a scoping review of online media reports. Issue 4 (7th April 2021) - Pearson, Isabelle; Butler, Nadia; Yelgezekova, Zhamin; Nihlén, Åsa; Yordi Aguirre, Isabel; Quigg, Zara; Stöckl, Heidi
Abstract : Objectives: This study aims to explore the strategies that governments and civil society organisations implemented to prevent and respond to the anticipated rise in violence against women and/or children (VAWC) during the 2019 novel coronavirus (COVID-19) pandemic. Design: A scoping review and content analysis of online media reports. Setting: WHO European region. Methods: A scoping review of media reports and publications and a search of other grey literature (published from 1 January to 17 September 2020). Primary and secondary outcome measures included measures implemented by governments, public services and non-governmental and civil organisations to prevent or respond to VAWC during the early months of the COVID-19 pandemic. Results: Our study found that in 52 of the 53 member states there was at least one measure undertaken to prevent or respond to VAWC during the pandemic. Government-led or government-sponsored measures were the most common, reported in 50 member states. Non-governmental and other civil society-led prevention and response measures were reported in 40 member states. The most common measure was the use of media and social media to raise awareness of VAWC and to provide VAWC services through online platforms, followed by measures taken to expand and/or maintain helpline services for those exposed to violence. Conclusion: The potential increase in VAWC during COVID-19-imposed restrictions and lockdowns resulted in adaptations and/or increases in prevention and response strategies in nearly all member states. The strength of existing public health systems influenced the requirement and choice of strategies and highlights the need for sustaining and improving violence prevention and response services. Innovative strategies employed in several member states may offer opportunities for countries to strengthen prevention and responses in the near future and during similar emergencies.